Perceptions of physicians caring for pediatric patients with cancer in Europe: insights into the use of palliative care, its timing, and barriers to early integration - Lacerda, Ana; Bravo-Carretero, Isabel M.; Ehrlich, Bella S.; Job, Godwin; Avilés Martínez, María; Leiss, Ulrike; Kokkinou, Georgia; Scheinemann, Katrin; Craig, Finella; Krottendorfer, Kerstin; Devidas, Meenakshi; Baker, Justin N.; et al. (Frontiers in Oncology, 2024)
BackgroundIntegrating pediatric palliative care (PPC) into pediatric oncology standard care is essential. Therefore, it is important to assess physicians’ knowledge and perceptions of PPC to optimize its practice.ObjectiveTo evaluate the knowledge, comfort levels, and perspectives of physicians regarding the timing and perceived barriers to integrating PPC into pediatric cancer care across Europe.DesignThe Assessing Doctors’ Attitudes on Palliative Treatment (ADAPT) survey, originally developed for other global regions, was culturally and contextually adapted for Europe.Setting/SubjectsThe survey was distributed via the European Society of Paediatric Oncology (SIOPE) membership listserv. Any physicians caring for children with cancer across Eastern, Southern, Central, and Northern Europe were invited to complete the survey.ResultsA total of 198 physicians from 29 European countries completed the ADAPT survey. Physicians demonstrated relative agreement with the World Health Organization’s guidance; median alignment was 83.4% (range 59.9%-94.1%). Although most respondents felt comfortable addressing physical (84.4%) and emotional (63.4%) needs, they felt less comfortable addressing spiritual needs (41.9%) and providing grief and bereavement support (48.5%). There were significant regional differences, such as physicians in Eastern and Southern Europe reporting a lack of PPC specialists, opioids, and home-based care, while those in Northern and Central Europe did not.ConclusionPhysicians caring for children with cancer throughout Europe have a good understanding of PPC. However, misconceptions about PPC persist, requiring educational and capacity-building efforts. Additionally, the regional differences in perceived barriers must be addressed to ensure equitable access to PPC for all European children with cancer.